Identification of the parental origin of the chromosomes in the natural interspecific hybrids in Colocasia using cytogenetic and molecular cytogenetic techniques - Viet, Nguyen Xuan (Academia Journal of Biology, 2015)
Two species of the genus Colocasia, C. esculenta and C. gigantea, can be hybridized, but data on the extent of the hybridization under natural conditions are not available to date. In the previous paper, we have reported the investigation of the natural interspecific hybrids in the genus Colocasia using isozymes [5]. The present study was carried out to identify the parental origin of the chromosomes in the natural hybrids in Colocasia, using the cytogenetic and molecular cytogenetic techniques (GISH). The cytogenetic analysis showed those natural interspecific hybrids having 28 chromosomes. The chromosome size ranged from 1.72~3.75 mm and one satellite pair with different size. These mitotic chromosome characters were consisted in the karyotypic characters of both C. esculenta and C. gigantea. The multiunivalent observed in pollen mother cells of the hybrids and their pollen fertilizer was too small indicated an abnormal in meiosis and suggested different chromosome origins in the hybrid cells. The GISH using the DIG-labeled total DNA of one species as a probe and the non-labeled DNA of the other species as a blocking DNA confirmed the origin of the chromosomes in the hybrids. The investigation of the natural hybrids and the identification of the parental origin of the chromosomes in these hybrids in our studies could provide useful information for the classification of taro varieties and the research of their phylogenetic relationships.